A comparative study of lateral and palmar venous anastomosis in Ishikawa zone Ⅱ fingertip replantation. (8th October 2020) - Li, Xuedong; Zhai, Huang; Zhao, Gang; Pan, Xiaoyun; Yao, Qun; Hua, Yong; Yu, Jiong; Mi, Jingyi
Purpose: Venous anastomosis is the key procedure for Ishikawa zone Ⅱ fingertip replantation. Both palmar and lateral veins provide efficient venous drainage. This study compared the clinical effects between these venous anastomoses for fingertip replantation. Methods: In 2016–2018, 61 patients underwent Ishikawa zone Ⅱ fingertip replantation with venous anastomosis (28 and 33 cases with palmar and lateral anastomoses, respectively). Retrospective comparative analyses evaluated surgical technique and function, including operative time; rates of finger survival, venous congestion, and infection; sensation; joint motion; cold intolerance symptom severity (CISS), Disabilities of the Arm, Shoulder, and Hand (DASH), and Vancouver scar scores; and chronic regional pain syndrome (CRPS) rates. Results: There were 33 patients with lateral vein anastomosis and 28 patients with palmar vein anastomosis. The average patient follow-up was 18.2 months. The survival rates did not differ significantly between groups (87.8% (29/33) vs. 85.7% (24/28), p > 0.05); however, the operative time was shorter in the lateral vein group than in the palmar vein group (78.57 ± 7.08 min vs. 67.88 ± 5.77 min, p < 0.05). Venous congestion and infection rates did not differ significantly between groups ( p > 0.05). The replanted finger function, including joint motion, sensation, DASH scores, Vancouver scar scores, and CRPS rates, did not differ significantly between groups ( p > 0.05). However, the CISS score was higher in the palmar vein group than in the lateral vein group (44.39 ± 5.16 vs. 38.09 ± 4.49, p < 0.05). Conclusions: Venous anastomosis with either palmar or lateral veins showed high survival rates and good function in fingertip replantation. The lateral vein had a shorter operative time and benefit to arterial revision and was especially suitable for patients with finger pulp damage.